Analyzing Phonemic Errors in Arabic by Native Javanese Speakers - Annisa, Wakhidatul; Nurbayan, Yayan; Saleh, Nalahuddin (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The complex system and characteristics of the hijaiyah letters make it difficult for non-native speakers to pronounce the letters. In addition, the differences in the phonological system of Indonesian and Arabic, including differences in phonemes between the two, have the potential to cause interference. This research aims to analyze and determine interference in the form of errors in pronunciation of Arabic phonemes by native Javanese speakers, word shifts, changes in word meanings, and loss of word meanings. The method used in this research is descriptive-qualitative. The research data comes from the reading results of two samples collected using listening and recording techniques, and the data is analyzed using the Praat application. The results of this research indicate that both samples made errors in the form of replacing one phoneme with another phoneme; the error in the pronunciation of the phoneme /ħ/ which causes the change in the pronunciation of the word حَسَدَ [ħasad] to هَسَدَ [hasad], the phoneme /ʕ/ which causes the change in the pronunciation of the word اَعُوْذُ [aʕu:ðu] to اَءُوْذُ [aʔu: ðu] and the phoneme /q/ which causes change in the pronunciation of the word فَلَقِ [falaq] to فَلَكِ [falak], meanwhile the two samples made no mistakes in pronouncing the phoneme /ʃ/ so there was no change in word or meaning in the word شَرِّ [ʃar.ri]. It is hoped that this research can become a source of Arabic language knowledge for Arabic language learners and the general public so that they know how important it is to pronounce Arabic phonemes well and correctly because it influences the meaning of the words being pronounced. Abstrak Kompleksnya sistem serta karakteristik huruf hijaiyah menjadi kesulitan tersendiri untuk para non penutur asli dalam melafalkan huruf-hurufnya. Selain itu, perbedaan sistem fonologi bahasa Indonesia dengan bahasa Arab, termasuk perbedaan fonem di antara keduanya, berpotensi menyebabkan interferensi. Penelitian ini bertujuan untuk menganalisis serta mengetahui interferensi yang berbentuk kesalahan pelafalan fonem bahasa Arab oleh penutur asli bahasa Jawa, pergeseran kata, perubahan makna kata, serta hilangnya makna kata. Metode yang digunakan dalam penelitian ini adalah deskriptif-kualitatif. Data penelitian bersumber dari hasil bacaan dua sampel yang dikumpulkan melalui teknik simak dan rekam, dan data dianalisis menggunakan aplikasi Praat. Hasil penelitian ini menunjukkan bahwa kedua sampel melakukan kesalahan berupa penggantian fonem yang satu dengan fonem yang lain; kesalahan pelafalan fonem /ħ/ yang menyebabkan perubahan pelafalan kata حَسَدَ [ħasad] menjadi هَسَدَ [hasad], fonem /ʕ/ yang menyebabkan perubahan pelafalan kata اَعُوْذُ [aʕu:ðu] menjadi اَءُوْذُ [aʔu:ðu] dan fonem /q/ yang menyebabkan perubahan pelafalan kata فَلَقِ [falaq] menjadi فَلَكِ [falak], sementara itu kedua sampel tidak melakukan kesalahan dalam melafalkan fonem /ʃ/ sehingga tidak ada penggantian kata ataupun makna pada kata شَرِّ [ʃar.ri]. Penelitian ini diharapkan dapat menjadi salah satu sumber pengetahuan bahasa Arab bagi para pembelajar bahasa Arab maupun masyarakat umum sehingga mereka mengtahui betapa pentingnya melafalkan fonem Arab dengan baik dan benar kareba hal itu memengaruhi makna kata yang dilafalkan.